A Novel Therapeutic siRNA Nanoparticle Designed for Dual-Targeting CD44 and Gli1 of Gastric Cancer Stem Cells - Yao H (Dove Medical Press, 2020)
Hongjuan Yao,1 Lan Sun,2 Jingcao Li,2 Xiaofei Zhou,1 Rui Li,1 Rongguang Shao,1 Yingge Zhang,2 Liang Li1 1Key Laboratory of Antibiotic Bioengineering of National Health and Family Planning Commission (NHFPC), Institute of Medicinal Biotechnology (IMB), Chinese Academy of Medical Sciences and Peking Union Medical College (CAMS & PUMC), Beijing 100050, People’s Republic of China; 2Key Laboratory of Nanopharmacology and Nanotoxicology, Beijing Institute of Pharmacology and Toxicology, Beijing 100850, People’s Republic of ChinaCorrespondence: Liang LiKey Laboratory of Antibiotic Bioengineering of National Health and Family Planning Commission (NHFPC), Institute of Medicinal Biotechnology (IMB), Chinese Academy of Medical Sciences and Peking Union Medical College (CAMS & PUMC), Beijing 100050, People’s Republic of ChinaTel +86 10-63165824Fax +86 10-63027302Email liliang@imb.pumc.edu.cnYingge ZhangBeijing Institute of Pharmacology and Toxicology, 27 Taiping Road, Haidian, Beijing 100850, People’s Republic of ChinaTel +86 10-66930654Fax +86 10-68211656Email zhangyg58@126.comPurpose: Gastric cancer stem cells (CSCs) are important for the initiation, growth, recurrence, and metastasis of gastric cancer, due to their chemo-resistance and indefinite proliferation. Herein, to eliminate gastric CSCs, we developed novel CSC-targeting glioma-associated oncogene homolog 1 (Gli1) small interfering RNA (siRNA) nanoparticles that are specifically guided by a di-stearoyl-phosphatidyl-ethanolamine- hyaluronic-acid (DSPE-HA) single-point conjugate, as an intrinsic ligand of the CD44 receptor. We refer to these as targeting Gli1 siRNA nanoparticles.Methods: We used the reductive amination reaction method for attaching amine groups of DSPE to aldehydic group of hyaluronic acid (HA) at the reducing end, to synthesize the DSPE-HA single-point conjugate. Next, targeting Gli1 siRNA nanoparticles were prepared using the layer-by-layer assembly method. We characterized the stem cellular features of targeting Gli1 siRNA nanoparticles, including their targeting efficiency, self-renewal capacity, the migration and invasion capacity of gastric CSCs, and the penetration ability of 3D tumor spheroids. Next, we evaluated the therapeutic efficacy of the targeting Gli1 siRNA nanoparticles by using in vivo relapsed tumor models of gastric CSCs.Results: Compared with the multipoint conjugates, DSPE-HA single-point conjugates on the surface of nanoparticles showed significantly higher binding affinities with CD44. The targeting Gli1 siRNA nanoparticles significantly decreased Gli1 protein expression, inhibited CSC tumor spheroid and colony formation, and suppressed cell migration and invasion. Furthermore, in vivo imaging demonstrated that targeting Gli1 siRNA nanoparticles accumulated in tumor tissues, showing significant antitumor recurrence efficacy in vivo.Conclusion: In summary, our targeting Gli1 siRNA nanoparticles significantly inhibited CSC malignancy features by specifically blocking Hedgehog (Hh) signaling both in vitro and in vivo, suggesting that this novel siRNA delivery system that specifically eliminates gastric CSCs provides a promising targeted therapeutic strategy for gastric cancer treatment.Keywords: Hedgehog (Hh) pathway, Gli1 siRNA, gastric cancer stem cells, di-stearoyl-phosphatidyl-ethanolamine-hyaluronic acid (DSPE-HA) single-point conjugate, therapeutic siRNA nanoparticles